Role of adenosine deaminase enzyme (ADA) in differentiating tuberculous pleural effusion from malignant pleural effusion - Rasheed, Haroon ur (ADVANCES IN BASIC MEDICAL SCIENCES, 2019)
Objective: To study the role of Adenosine deaminase enzyme (ADA) in differentiating tuberculous pleural effusion from malignant pleural effusion. Material and Methods: It was a cross sectional descriptive study carried out in Pulmonology departments of Lady Reading Hospital, Khyber teaching Hospital Peshawar and department of Pathology, Khyber Medical College, Peshawar from April 2015 to Jan 2016. A total of 128 patients including 88 tuberculous and 40 malignant pleural effusion patients were selected through consecutive non-probability sampling technique. Results: In our study, mean ADA levels in pleural fluid were significantly higher for tuberculous than for malignant pleural effusions (p<0.001 ).Pleural fluid ADA levels has sensitivity, specificity, PPV and NPV of 95.5%, 90%, 95.4%, and 50% respectively in differentiating tuberculous pleural effusions from malignant pleural effusion. Conclusion: Tuberculosis is the commonest infectious disease worldwide .A pleural fluid ADA level of ≥ 35 U/L in lymphocyte predominant effusions makes mycobacterium tuberculosis most likely etiology. This test is not only very sensitive and specific but also is very cheap, quick and easy to perform by routine colorimetric method. Key words: Tuberculosis, Pleural effusion (P.E), Adenosine deaminase enzyme (ADA), sensitivity, specificity, Positive predictive value (PPV) and negative predictive values (NPV).